The effect of metacognitive strategies on student attitude toward reading - Euler, Kathryn (My University, 2018)
The purpose of this study was to determine the effect of metacognitive strategies on students' attitude toward learning, with the strategies and learning experiences being specifically related to learning about reading. The three strategies that were explicitly taught were: previewing the text, questioning, and summarizing. Student surveys were conducted prior to learning a metacognitive strategy, and again after having time to put that strategy in place while reading independently. Data was gathered and coded to search for a correlation between explicitly learning and implementing a metacognitive strategy and improving students' attitude toward learning experiences related to reading. Most attitudes recorded on the surveys remained consistent throughout the study, but one trend emerged. On average, Students reported a positive change on each post survey on the prompt "This strategy made me a better reader". While explicitly teaching metacognitive strategies did increase student awareness of the learning process, this study did not implicate a noticeable impact on their attitude toward learning.
Keywords: Literacy; Reading instruction; Teaching